PENGARUH MODEL PEMBELAJARAN BERBASIS PRAKTIK TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM DI SMP NEGERI 2 GALESONG SELATAN - Muh. Albar; Fajri; Nasir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of practice-based learning models on students' learning interest in science subjects at SMP Negeri 2 South Galesong. The study used a quantitative descriptive method with a Likert scale questionnaire given to 30 students of class IX D through a purposive sampling technique. The results showed that the practice-based learning model was able to increase students' learning interest, marked by increased enthusiasm, activeness, and understanding of students during experimental activities. Students were more motivated and involved when learning science concepts through direct experience. These findings confirm that practice-based learning is effective in strengthening students' learning interest.